2010
DOI: 10.1074/jbc.m110.117069
|View full text |Cite
|
Sign up to set email alerts
|

NuA4-dependent Acetylation of Nucleosomal Histones H4 and H2A Directly Stimulates Incorporation of H2A.Z by the SWR1 Complex

Abstract: Structural and functional analyses of nucleosomes containing histone variant H2A.Z have drawn a lot of interest over the past few years. Important work in budding yeast has shown that H2A.Z (Htz1)-containing nucleosomes are specifically located on the promoter regions of genes, creating a specific chromatin structure that is poised for disassembly during transcription activation. The SWR1 complex is responsible for incorporation of Htz1 into nucleosomes through ATP-dependent exchange of canonical H2A-H2B dimer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
159
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(174 citation statements)
references
References 57 publications
12
159
0
3
Order By: Relevance
“…The loss-of-function pie1 mutant flowers early because PIE1 is required for the deposition of H2A.Z at FLC, MAF4, and MAF5 (Deal et al, 2007). NuA4, the only essential histone acetyltransferase complex in S. cerevisiae, acetylates the N-terminal tails of histones H4 and H2A, which directly stimulates the incorporation of H2A.Z by the SWR1 complex (Altaf et al, 2010). Yaf9 is a component of the NuA4 and SWR1 complexes, can bind histones H3 and H4 in vitro, and is required for histone variant H2A.Z deposition and for H2A.Z and H4 acetylation (Zhang et al, 2004;Altaf et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The loss-of-function pie1 mutant flowers early because PIE1 is required for the deposition of H2A.Z at FLC, MAF4, and MAF5 (Deal et al, 2007). NuA4, the only essential histone acetyltransferase complex in S. cerevisiae, acetylates the N-terminal tails of histones H4 and H2A, which directly stimulates the incorporation of H2A.Z by the SWR1 complex (Altaf et al, 2010). Yaf9 is a component of the NuA4 and SWR1 complexes, can bind histones H3 and H4 in vitro, and is required for histone variant H2A.Z deposition and for H2A.Z and H4 acetylation (Zhang et al, 2004;Altaf et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…NuA4, the only essential histone acetyltransferase complex in S. cerevisiae, acetylates the N-terminal tails of histones H4 and H2A, which directly stimulates the incorporation of H2A.Z by the SWR1 complex (Altaf et al, 2010). Yaf9 is a component of the NuA4 and SWR1 complexes, can bind histones H3 and H4 in vitro, and is required for histone variant H2A.Z deposition and for H2A.Z and H4 acetylation (Zhang et al, 2004;Altaf et al, 2010). Our results show that Arabidopsis YAF9a is required for H4 acetylation and the deposition of H2A.Z at GI, indicating that Arabidopsis YAF9a might be the counterpart of yeast Yaf9 and that YAF9a is involved in chromatin and transcriptional regulation at GI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the lethal phenotype caused by quadruplet mutations of all four lysine residues (H4K5, 8,12,16) within the H4 N-tail, which cannot be recapitulated with any combination of triple mutations on the lysines, indicates the redundancy of all four lysine residues for cell viability (17). Furthermore, triple mutations on lysines within H4 N-tail (H4K5, 8,12) in combination with deletion of H3 N-tail, which carries five acetylatable lysines (H3K9, 14,18,23,27), causes cellular lethality (12). Similarly, double deletion of the H2A/H2B or of the H3/H4 N-tails is lethal (18,19).…”
mentioning
confidence: 99%
“…More recently, ANP32E was identified as another H2A.Z-specific chaperone that removes H2A.Z from enhancer regions in mammalian cells [53, 54•]. The Swr1 complex binds to acetylated histones in general to preferentially deposit H2A.Z at acetylated regions of the genome [55]. However, recent studies by Ranjan et al showed that recognition of a nucleosome-free region by the Swr1 complex was more efficient for its targeting to DNA than recognition of acetylated chromatin [56].…”
Section: H2az Localization and Depositionmentioning
confidence: 99%